Avaliação convencional e estesiômetro: resultados controversos na avaliação sensitiva no câncer de mama - Ornelas, Fernanda Aparecida de; Rodrigues, José Ricardo Paciência [UNESP]; Uemura, Gilberto [UNESP] (My University, 2010)
This study, clinical, prospective, randomized study was conducted from August 2004 to February 2008 in a convenience sample of 60 women who underwent breast surgery with axillary dissection, divided into two groups (n = 30). The GI (Guidance Kit with different textures, to perform at home) and GII (control). The objective was to analyze the effect of home orientation in patients after surgery for breast cancer complaining of numbness, evaluation, and the conventional esthesiometer. The surface sensitivity was assessed by monofilament Semmes-Weinstein and evaluation using conventional two test tubes with hot water (38 to 43o C) and cold (16 to 27o C), paintbrush, needle. The GI was subjected to 10 sessions and assessments in both 3 times. The M1 (pre intervention), the M2 (post-intervention) after 10 sessions of physical therapy intervention and M3 (washout) after 3 months the second time for assessment. The region targeted for evaluation and intervention was the sensory nerve dermatome intercostobrachial. In the test of Goodman (conventional assessment) there was improvement in both groups, the P1, during the thermal evaluation. The t-test of student (esthesiometer) there was improvement in P2 only in GI (p = 0.003) between points 1 and 2 while the time 3 (p = 0.121 and p = 0.733 respectively). It was concluded that there were divergent and opposite results after examining the effect of home orientation in the nerve dermatome intercostobrachial, evaluation, and the conventional esthesiometer.

Este estudo clínico, prospectivo e randomizado, foi realizado no período de agosto de 2004 a fevereiro de 2008, na amostra de conveniência de 60 mulheres, submetidas à cirurgia de mama com esvaziamento axilar, divididas em dois grupos (n=30): o GI (Orientação com Kit de diferentes texturas, para realização em domicilio) e o GII (Controle). O objetivo foi analisar o efeito da orientação domiciliar, em pacientes após cirurgia de câncer de mama com queixa de hipoestesia, pela avaliação convencional e com o uso do estesiômetro. A sensibilidade superficial foi avaliada pelos monofilamentos de Semmes-Weinstein e pela avaliação convencional utilizando dois tubos de ensaios com água quente (38 a 43o C) e fria (16 a 27o C), pincel e agulha. O GI foi submetido a dez sessões e ambos a avaliações em três momentos. O M1 (Pré intervenção), o M2 (Pós-intervenção) após dez sessões de intervenção fisioterapêutica e o M3 (washout) após três meses do segundo momento avaliativo. A região alvo de avaliação e intervenção sensitiva foi o dermátomo do nervo intercostobraquial. No teste de Goodman (avaliação convencional) houve melhora em ambos os grupos no P1, durante a avaliação térmica. No teste “t” de student (estesiômetro) houve melhora no P2 apenas no GI (p=0,003) entre os momentos um e dois mantendo no momento três (p=0,121 e p=0,733 respectivamente). Foi concluído que houve divergência e resultados opostos, após analisado o efeito da orientação domiciliar no dermátomo do nervo intercostobraquial, pelas avaliações convencional e com uso do estesiômetro.
Evaluation conventional and esthesiometer: controversial results in sensory evaluation in breast cancer
Keywords: Monofilament Semmes-Weinstein; Conventional evaluation; Breast cancer; Monofilamentos de Semmes-Weinstein; Avaliação convencional; Câncer de mama